Удмуртия: от А до Я / составители В. Ю. Семёнов, Г. Г. Грязев ; [фотографы: Н. А. Глухов [и др.] - Семенов Валентин Юрьевич (Удмуртия, 2021)
Экземпляры: ЦБ (20230504) / Инвентарный номер: 56583 / Цена: 400.00 / Сис.шифр: 26.89(2Рос.Удм) / Авт.знак: У 30 / ГРНТИ: 39.23 / ББК: 26.89(2Рос.Удм)